Keberagaman Sosial sebagai Fondasi Karakter dan Toleransi Siswa Sekolah Dasar - I Ketut Satria Ardana; Dewa Bagus Sanjaya; I Nengah Suastika (Cetta: Jurnal Ilmu Pendidikan, 2026)
Social diversity is an inherent characteristic of the elementary school environment and has significant potential as a foundation for fostering students' character development and tolerance. This article aims to systematically examine research findings on the role of social diversity in elementary schools in promoting students' character and tolerance. The study employed a qualitative literature review using content analysis. The literature search was conducted through Google Scholar, ERIC, and Scopus databases using the keywords social diversity, elementary school, character education, tolerance, keberagaman sosial, sekolah dasar, and pendidikan karakter. The included sources consisted of peer-reviewed journal articles and books published between 2021 and 2026 in both Indonesian and English, focusing on social diversity in elementary school settings and available in full text. Irrelevant, duplicate, and non-peer-reviewed publications were excluded from the analysis. The review revealed that social diversity in elementary schools encompasses differences in religion, ethnicity, culture, language, socioeconomic background, gender, and individual characteristics. The synthesis of the selected studies indicates that social diversity contributes to strengthening students' character by fostering tolerance, empathy, cooperation, responsibility, social awareness, and mutual respect. The development of tolerance is facilitated through inclusive social interactions, collaborative learning, multicultural value habituation, and teachers' role modeling in creating a learning environment that respects diversity. The findings highlight that social diversity is not merely a reality of elementary education but also serves as a fundamental basis for developing inclusive educational practices that support students' character development.